Breaking the glass ceiling: an interview with Dr. Shirley Graves, a pioneering woman in medicine. Issue 4 (26th February 2014) - Ahmed, Zulfiqar; Mai, Christine L.; Elder, Badrea; Rodriguez, Samuel; Yaster, Myron
Summary Shirley Graves M.D., D.Sc. (honorary) (1936), Professor Emeritus of Anesthesiology and Pediatrics at the University of Florida, was one of the most influential women in medicine in the 1960 and 1970s, a time when the medical profession was overwhelmingly male‐dominated. In today's society, it is hard to believe that only 50 years ago, women were scarce in the field of medicine. Yet Dr. Graves was a pioneer in the fields of pediatric anesthesia and pediatric critical care medicine. She identifies her development of the pediatric intensive care unit and her leadership in the Division of Pediatric Anesthesia at the University of Florida as her defining contributions. Through her journal articles, book chapters, national and international lectures, and leadership in the American Society of Anesthesiology and the Florida Society of Anesthesiology, she inspired a generation of men and women physicians to conquer the unthinkable and break through the glass ceiling.